The making of inclusive value chains insights from service delivery initiatives in Ghana’s cocoa chain - Obeng Adomaa, F. (Wageningen University & Research, 2023)
For many decades, integrating smallholder farmers into global value chains has not univocally delivered the assumed benefits to them. In response, there have been calls for value chain actors to deliberately work towards being more inclusive as a condition for delivering benefits to smallholders. In the global cocoa chain, this has resulted in the construction and implementation of sustainability programmes and certification schemes and the set-up of associated service delivery initiatives to smallholders. Despite the proliferation of these programmes, it is not evident how inclusion is configured in specific contexts. Predominantly, inclusiveness refers to an ethical frame, which leads to a focus on analysing inclusiveness as a predefined outcome. Little attention is given to examining the processes and mechanisms that configure inclusiveness and generate consequential outcomes. Emphasis on outcomes, however, risks simplifying analysis of inclusiveness into pros versus cons discussions, which does not advance our understanding of how inclusiveness is configured in value chains initiatives. This thesis unpacks the composite dynamics of the making of inclusive value chain initiatives. Specifically, the thesis unpacks the configuration of inclusiveness as an emergent outcome of interactions among actors located at different layers of the value chain. The empirical entry for analysing the configuration of inclusiveness is service delivery initiatives (SDIs), which is done by companies, civil society organisations and farmer-based organisation delivering services to smallholders in the cocoa sector in Ghana. The thesis answers two main research questions: 1) how is inclusiveness configured in a multi-actor service delivery initiative embedded in a global value chain? 2) how do actors navigate the conditions in their contexts to mediate interactions that configure inclusiveness?. Chapter 2 contextualises the making of inclusiveness in the historical and evolving institutional setting of Ghana’s cocoa sector. The chapter highlights how global dynamics in the chain connect to the national setting where the Ghanaian state is a key player and regulator of the chain through its parastatal, the Ghana Cocoa Board. The chapter highlights the emergence of cocoa sustainability programmes and initiatives and shows how the implementation of these programmes creates convergence of multiple contexts into a public-private hybrid institutional setting. It anchors SDIs within this global-national institutional setting and foregrounds the subsequent empirical chapters in the dynamics of the global-national cocoa chain. The pressure to ensure sustainability and justice has provoked mutually dependent relationships between firms and farmers in the cocoa chain. Chapter 3 takes a critical look at how terms of inclusion are configured in the refashioned relationship between firms and farmers and refashioned their hitherto remote relationship. The chapter answers the question: what interactions between firms and farmers configure procedural and distributive justice and foster inclusiveness in value chain initiatives? The chapter outlines the implications of the refashioned relationship for procedural justice principles of interdependence and refutability, and the distributive justice principles of need and equity. These principles are important enablers of different Summary 155 dimensions of inclusion: ownership, voice, risk, and reward. The chapter qualifies the making of inclusiveness in five service delivery initiatives. The chapter demonstrates how terms of inclusion emerge as an outcome of a interactions that are constantly reworked in response to smallholder farmers’ agency and state regulations. Service delivery on good agricultural practices (GAPs) is assumed to lead the way for sustainable cocoa production. Yet, the uptake of GAPs by cocoa farmers is persistently low. Chapter 4 examines the low uptake of a specific GAP, namely pruning. The chapter answers the question: what enables pruning to be and constrains it from being made relevant to and translated into farmers repertoires. The chapter uses the concepts of affordances and inscription to provide an account of the vertically coordinated travel of pruning from the site of research through extension to farming. The chapter reframes the adoption problems. It exposes a misfit emerging in the enactment of pruning practices at different sites in the agricultural research value chain. The chapter highlights the necessity of enabling fit to make GAPs relevant for farmers and promote their uptake. Chapter 5 confronts the issue of persistent indebtedness among cocoa farmers in Ghana and the associated narrative of eliminating middlemen as a route to reduce farmer indebtedness. The chapter answers the question: what practices and conditions reproduce the indebtedness of cocoa farmers in Ghana? This question is closely linked to the question what complicates changing indebtedness. The chapter presents the intricacies of the producer-intermediary relationship highlighting how these are constituted by material dimensions, such as time, space, and quantityquality requirements. This leads to a social-material account that exposes both cooperation and tensions in the producer-intermediary relationship. The paradoxical situation highlights interdependencies and entanglements and explains the persistence of indebtedness. The chapter explains why an exclusive actor perspective, putting the blame on the intentionality of the middlemen, is unable to open the ‘black box’ of intermediation and consequently possibly fosters policy misdirection. Chapter 6 brings insights from the chapters together to highlight interactions among actors and conditions that mediate interactions to configure inclusiveness. The chapter distinguishes different types of configurations: multiple and interdependent vulnerabilities, material and institutional realities, and written and unwritten rules. As a forward-looking agenda, the thesis presents a combination of configurational and institutional perspectives to deepen our understanding of the ingredients that come together in the making of inclusive value chain initiatives. Having a configurational and institutional understanding of inclusiveness opens space to a more robust insight on how inclusiveness of value chain initiatives is made and how this is contingent on context. It also opens space to know which aspects of the configurations to intervene on, and where to intervene in layered global commodity chains to foster inclusiveness outcomes.